Multi-Media Exposure, Selective Accumulation and Health Risks of Organochlorine Pesticides in Human Serum under Post-Ban Conditions - Yuhao Fan; Lei Hou; Kecheng Guo; Ye Wu; Chen Guo; Xinyu Lou; Dan Chen; Junjie Jiang; Moson Dalutai; Yongjie Wei; Jun Jin (Environmental Contamination: Causes and Solutions, 2026)
Organochlorine pesticides (OCPs), despite being banned, persist in the environment and continue to pose potential risks to human health. This exploratory study investigated the concentrations of multiple OCPs in serum samples from 10 local residents and 52 surrounding environmental samples, including soil (n = 10), air (n = 12), indoor dust (n = 10), and food (n = 20), collected in Taizhou, Zhejiang Province, in 2022. Multiple exposure pathways were quantified, and associated health risks were assessed. The results showed evidence of selective accumulation in humans, with serum ΣOCP concentrations ranging from 107.01 to 552.41 ng/g lipid weight (lw). p,p′-DDE was the predominant compound, accounting for 67.81% of total serum OCPs, while β-HCH showed relatively higher enrichment among HCH congeners. Lower proportions of p,p′-DDT and α-/γ-HCH were observed. Source contributions varied across media: food was the primary contributor to p,p′-DDE exposure, indoor dust and soil contributed more to β-HCH and certain DDT isomers, and the atmosphere showed a higher contribution of methoxychlor. Differences between integrated exposure profiles and serum composition highlighted the potential roles of metabolic transformation and lipid-associated accumulation in shaping internal OCP burdens. Risk assessment indicated that DDT metabolites and β-HCH were the major contributors to potential exposure risks. Overall, this study provides preliminary insights into the environmental–human distribution patterns of OCPs observed in Taizhou under post-ban conditions and highlights that environmental concentrations alone may not fully represent chronic internal exposure. These findings improve the understanding of potential OCP exposure pathways and emphasize the need for larger-scale studies incorporating population characteristics and refined exposure parameters for more comprehensive risk assessment